The Impact of Strategic Leadership on Enhancing Organizational Reputation: A Field Study on Administrative Employees at King Abdulaziz University in Jeddah Governorate - Al-Zahrani, Saleh Jamaan Saleh (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to examine the impact of strategic leadership (strategic orientation, organizational culture, human capital, ethical practices, and organizational control) on enhancing organizational reputation from the perspective of employees at King Abdulaziz University. The research problem focused on addressing a gap in the literature, as there were no previous studies tackling this subject, particularly within the context of King Abdulaziz University. The significance of the study lies in enriching the Arabic and Saudi academic libraries with research in this field, as well as contributing to achieving the desired outcomes in strengthening the organizational reputation within King Abdulaziz University. The study sought to test the main hypothesis: there is a statistically significant impact of strategic leadership on enhancing organizational reputation at a significance level of 0.050 α ≤ from the perspective of King Abdulaziz University employees in Jeddah. The study adopted a descriptive-analytical methodology and used a questionnaire as the primary tool for data collection from a random sample of administrative employees at the university’s Al-Sulaimaniah campus in Jeddah. The sample size reached (344) respondents. Data were analyzed using the SPSS program. The results showed that the level of strategic leadership at King Abdulaziz University was rated very high. The dimension of ethical practices ranked first with a mean of (4.75), followed by strategic orientation with a mean of (4.41), then human capital with a mean of (4.40), and finally organizational culture with a mean of (4.35). Additionally, the results revealed that the level of organizational reputation at King Abdulaziz University was also rated very high. Significant differences were found at the (0.05) level in the mean responses regarding strategic leadership based on the gender variable, with males having a higher mean compared to females. Differences were also found in responses regarding both strategic leadership and organizational reputation according to the job title variable, with discrepancies observed particularly between the "other" job category and the listed job titles.